Exploring the factors affecting mental health and digital cultural dependency among university students - Ting Tin Tin; Winnie Chin; Lim Le Xin; Yuen Siu Mei; Chaw Jun Kit; Wan Nor Al-Ashekin Wan Husin; Ali Aitizaz; Lee Kuok Tiung; Ayodeji Olalekan Salau; Umar Farooq Khattak; Yasin Ahmed Siddiqui (Scopus, 2024)
Mental health problems have become a big problem among university students. However, university students will easily neglect the severity of mental health problems and why they cause mental health problems. Therefore, we are going to investigate how factors such as family socioeconomic and family parenting style affect students' mental health. Besides that, in this digital technology era, university students can easily have digital cultural dependency. Therefore, we also investigate whether mental health problems among university students cause digital cultural dependency. We collect data for this study from TARUMT students, which is done by distributing questionnaires on various social media sites, including Facebook, Instagram, and XiaoHongShu. A total of 165 respondents participated in the questionnaire. The data was cleaned and statistically analyzed using SPSS. According to the result of this research, there is no significant relationship between family socioeconomic and academic stress, financial stress, general stress, anxiety, depression, and digital culture dependency. Moreover, there are also no significant relationships between family parenting style and academic stress, financial stress, general stress and digital cultural dependency. In addition to this, the family parenting style has a significant impact on depression and anxiety. Then, the result of this research found that academic stress, financial stress, general stress, anxiety, and depression have a significant impact on digital culture. This research presents new perspectives for undergraduates on their mental health and digital cultural dependency. This is useful as a guide for policy makers in the future to improve mental health problems.